KONSTRUKSI SOSIAL TERHADAP PEREMPUAN SEBAGAI PEMIMPIN DALAM PEMILIHAN GUBERNUR JAWA TIMUR 2024 - Della Nur Safitri; Ahmad Ridwan (Jurnal Analisa Sosiologi, 2024)
This research examines how gender stereotypes shape the social construction of women as leaders, often perceiving them as less competent than men. Focusing on the 2024 East Java Gubernatorial Election, where all candidates are women, the study aims to understand university students' perceptions of women's leadership. It analyzes the influence of patriarchal norms on these perceptions and explores how views may vary based on gender, cultural background, and geography. Utilizing Peter L. Berger's social construction theory, which consists of three stages—externalization, objectivation, and internalization—the study employs a qualitative approach, conducting in-depth interviews. The research involved 12 participants: six students with East Java ID cards and six students from outside East Java who are currently studying in Surabaya. Participants were selected through purposive sampling to ensure representation from various study programs and included individuals aged 18 to 25. This approach aimed to encompass a diverse range of social, educational, and geographical backgrounds. The data were analyzed thematically through processes of data reduction, presentation, and conclusion drawing. The results indicate that gender stereotypes remain a significant obstacle, particularly among male students who tend to be skeptical of women's leadership abilities. However, progressive views are starting to emerge, especially among female students and the younger generation, who evaluate leadership based on individual competence rather than gender. The 2024 East Java gubernatorial election is viewed as a crucial opportunity to shift the patriarchal social construct toward greater gender equality.